EISCAT and Cluster observations in the vicinity of the dynamical polar cap boundary - A. T. Aikio (Annales Geophysicae, 2008)
The dynamics of the polar cap boundary and auroral oval in the nightside ionosphere are studied during late expansion and recovery of a substorm from the region between Tromsø (66.6° cgmLat) and Longyearbyen (75.2° cgmLat) on 27 February 2004 by using the coordinated EISCAT incoherent scatter radar, MIRACLE magnetometer and Cluster satellite measurements. During the late substorm expansion/early recovery phase, the polar cap boundary (PCB) made zig-zag-type motion with amplitude of 2.5° cgmLat and period of about 30 min near magnetic midnight. We suggest that the poleward motions of the PCB were produced by bursts of enhanced reconnection at the near-Earth neutral line (NENL). The subsequent equatorward motions of the PCB would then represent the recovery of the merging line towards the equilibrium state (Cowley and Lockwood, 1992). The observed bursts of enhanced westward electrojet just equatorward of the polar cap boundary during poleward expansions were produced plausibly by particles accelerated in the vicinity of the neutral line and thus lend evidence to the Cowley-Lockwood paradigm.